Langmuir-Blodgett monolayer of electrochemically synthesized PANI-TiO2 nanocomposites for MSG biosensor - Sharma, Devdutt; Dutta, Hemant Sankar; Dhayal, Marshal (Elsevier B.V., 2022)
Nanocomposites of polyaniline titanium oxide (PANI-TiO2) have been synthesized by employing the electrochemical technique and their monolayers were prepared on a pre-chemical treated indium tin oxide (ITO) surface through Langmuir-Blodgett (LB) process. The TEM images show the well dispersion of an average ∼ 5 nm diameter TiO2 particles in the film of PANI-TiO2 with ∼ 0.35 nm interatomic spacing of titanium atoms in the anatase crystalline plane (101). X-ray photoelectron (XPS) spectra of LB film of PANI-TiO2 also confirmed the presence of Ti atoms as a similar observation was also confirmed in energy dispersive X-ray analysis (EDX) analysis of the film surface. Electrochemical conductivity of the PANI-TiO2 LB films showed enhancement in peak current, and subsequent immobilization of monoclonal antibodies specific to L-glutamic acid was achieved. Differential pulse voltammetry (DPV) measurements showed a linear response in the peak current with MSG concentration varying from 1 nM to 500 µM and 1 µM to 250 µM in the electrolyte and tomato sauce, respectively. The detection sensitivity of the immunosensor was ∼ 37 mA/nM.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Polyaniline-TiO2 nanocomposite; Differential pulse voltammetry; Cyclic voltammetry; Electrochemical immunosensor; Langmuir-Blodgett; Mono-sodium glutamate